Analisis Kepuasan Masyarakat Terhadap Penggunaan Aplikasi SiBisa dengan Pendekatan TAM - T Lyza Tahura Chairunnisa; Enita Rosmika; Azulaidin Azulaidin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Beneficiaries of technological advances at this time have been widely used by many sectors such as health, education, government or even public services from an agency. Basically, government agencies adopt the principles of good government or good governance. What has always been the main focus of city government is on services to the Population and Civil Registration Service (DISDUKCAPSIL). The process carried out on civil registration has a main focus based on the process that is carried out for a long time and also requires the community to come back and forth to carry out the civil registration process. Pemko Medan has a vision and mission focus on improving public services. The Si Bisa application was developed by the Medan City Government to make it easier for the people of Medan City to take care of population administration. But the success and also the benchmark of government is not only from the ease of public services but also satisfaction with public services. This study aims to measure the level of community satisfaction with the service of the Sibisa application by approaching the Technology of Acceptance Model (TAM) method. With as many as 30 respondents from Sibisa application users. The results of the research show that the community is satisfied with the convenience and service of the Sibisa application. This is supported by the influence of the variable stimulant of 75.2%